2017
DOI: 10.1039/c7cs00076f
|View full text |Cite
|
Sign up to set email alerts
|

Surface point defects on bulk oxides: atomically-resolved scanning probe microscopy

Abstract: Metal oxides are abundant in nature and they are some of the most versatile materials for applications ranging from catalysis to novel electronics. The physical and chemical properties of metal oxides are dramatically influenced, and can be judiciously tailored, by defects. Small changes in stoichiometry introduce so-called intrinsic defects, e.g., atomic vacancies and/or interstitials. This review gives an overview of using Scanning Probe Microscopy (SPM), in particular Scanning Tunneling Microscopy (STM), to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 50 publications
3
83
0
Order By: Relevance
“…Bright features can be attributed to adatoms on top of the reconstructed ad-layer or oxygen hydroxyl (O−H) groups resulting from rest gases in the vacuum chamber, as it is known 44 that interstitial Ti atoms can cause a substantial increase in local surface reactivity and thus facilitate O−H group adsorption. Dark features could, on the other hand, indicate missing ad-islands in the reconstruction 11 , 45 or, considering that annealing was carried out at oxygen-poor conditions, more likely represent oxygen vacancies ( V O ) at or near the surface 42 , 46 . In agreement with that, the density of empty states 1 eV above Fermi level, which the STM probes, is high at all sites where a surface O atom is present.…”
Section: Resultsmentioning
confidence: 99%
“…Bright features can be attributed to adatoms on top of the reconstructed ad-layer or oxygen hydroxyl (O−H) groups resulting from rest gases in the vacuum chamber, as it is known 44 that interstitial Ti atoms can cause a substantial increase in local surface reactivity and thus facilitate O−H group adsorption. Dark features could, on the other hand, indicate missing ad-islands in the reconstruction 11 , 45 or, considering that annealing was carried out at oxygen-poor conditions, more likely represent oxygen vacancies ( V O ) at or near the surface 42 , 46 . In agreement with that, the density of empty states 1 eV above Fermi level, which the STM probes, is high at all sites where a surface O atom is present.…”
Section: Resultsmentioning
confidence: 99%
“…38 Indeed, iron oxides generally tend to deal with stoichiometric variation by varying the cation lattice, with the close-packed oxygen sublattice remaining intact, 38,70 and we have recently shown that the (√2 × √2)R45° reconstruction on Fe 3 O 4 (001) is based on a subsurface array of Fe vacancies and interstitials. 67 Nevertheless, several (2 × 1) models based on subsurface Fe atoms in octahedral interstitial sites were tested and found to be extremely unstable compared to models based on surface oxygen vacancies.…”
Section: Discussionmentioning
confidence: 99%
“…Many of their chemical and physical properties can be modified by the introduction of imperfections into their crystalline structure. The presence of dopants, defects or nonstoichiometry can induce variations in the oxide properties and significantly alter the final device performance . Research on different interfacial organic modifiers has gained attention due to their ability to influence oxide properties, tune their electrical, chemical, and physical properties, affect charge carrier dynamics (transport, injection, and recombination) or modify their work function.…”
Section: Introductionmentioning
confidence: 99%